Pendidikan Multikultural dalam Sirah Nabawiyyah: Pembelajaran untuk Masyarakat Majemuk - Biari, Dina Audina Hasan (Maliki Interdisciplinary Journal, 2024)
Multicultural education is an important approach in building an inclusive and harmonious society amidst cultural, ethnic and religious diversity. This article highlights the importance of multicultural education from an early age as an effort to reduce discrimination and conflict in Indonesia, which has complex cultural diversity. In the Islamic context, multicultural education has been taught by the Prophet Muhammad through various methods, including the Medina Charter which emphasizes the principles of justice, equality, and tolerance. The research method used is literature research, reviewing literature on multicultural education in Sirah Nabawiyyah. This article discusses the concept of multicultural education in Islam, the learning methods applied by the Prophet Muhammad, and the application of multicultural values in the modern context. Challenges in implementing multicultural education in Indonesia include resistance to change, lack of resources, and the existence of prejudice and stereotypes. Solutions include continuing education, open dialogue, teacher training and inclusive curriculum development. Multicultural education can help create an inclusive and harmonious society and prepare individuals to live in cultural diversity with mutual respect and appreciation.